Comparative assessment of the depth of invasion of early-stage oral cavity carcinomas based on intraoral ultrasound and computerized tomography findings - Marković Vasiljković, Biljana; Antić, Svetlana; Jelovac, Drago (Vojnosanitetski pregled, 2023)
Background/Aim. The depth of invasion of oral cavity carcinoma (OCC) and the nodal involvement define the treatment selection, outcome, and prognosis of the disease. In determining the stage of OCC, the most widely applied methods are computerized tomography (CT) and magnetic resonance imaging (MRI), whose limitations can be overcome to some extent by using intraoral ultrasound (IOUS). The aim of the study was to evaluate the imaging presentation of early-stage OCC, determine the depth of invasion (DOI) and the greatest diameter (GD) of the tumor using the IOUS and CT methods, and compare them with histopathological (HP) findings. Methods. The study was designed as a prospective one, with a time limitation of three months. Eleven patients with clinical early-stage OCC underwent a native CT examination of the head and neck as well as a contrast-enhanced phase, and then IOUS of the lesion was performed. Using both methods, DOI and GD values were measured, and the values were correlated with HP findings. The analysis of the obtained data was performed using the statistical package SPSS 22 and Pearson correlation coefficient. Results. A significant correlation (p = 0.001) was established between the DOI values measured by IOUS and CT examination with the measurements obtained by HP processing. On the other hand, by comparing the GD measured on IOUS and CT examination, no correlation was established with the HP report. Conclusion. Measurements of DOI obtained by IOUS significantly correlated with those in the HP report, while overcoming the limitations of the CT method in the evaluation of small-sized tumors and tumors that cannot be shown due to artifacts.
Keywords: histological techniques; mouth neoplasms; neoplasm invasiveness; tomography, x-ray computed; ultrasonography